Performance Analysis of a High Gain LUO Converter-Based Hybrid PV-Wind System - Amutha Priya, N.; Aswin, M.; Azis Shane, S. J.; Blessing Dino, Y.; Dagul, D. (Asian Journal of Electrical Sciences, 2021)
This project is aimed at the implementation of a fuzzy logic algorithm based maximum power point tracking in transformer less grid connected PV system along with reactive power compensation. A single diode model is used for PV array and its simulation is performed using MATLAB. In fuzzy logic controller, voltage and current are taken as inputs and the effective value of A.C current corresponding to the maximum power point is obtained as output. Thus, in addition to supplying voltage by the inverter without transformer for compensating the reactive power not exceeding its power rating. This results in utilization of PV system at night and at periods of low irradiation. Rules relating the input and output of fuzzy logic controller are written and simulation is performed. A LUO Converter is used for maintaining DC input to the inverter at various conditions of irradiation and temperature. Gating pulses to the inverter are generated by proportional-integral controller. Hardware model of a10W solar panel is developed and results are obtained with fuzzy logic controller for different irradiation and temperature conditions. Results show the effectiveness of the proposed method in utilizing the PV system. This project is implemented using DSPIC30F2010 controller.